Effect of alkaline salts on the quality characteristics of yellow alkaline noodles. (November 2018) - Fan, Huiping; Ai, Zhilu; Chen, Yuehua; Fu, Feng; Bian, Ke
Abstract: The quality of yellow alkaline noodles was characterized by studying the changes in the cooking and textural properties upon addition of alkaline salts to the flour while making the noodles. Protein components, pasting property, microstructure, free sulfhydryl (SH) content, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis were performed to investigate the mechanisms underlying their quality differences. The results indicated that the addition of alkaline salts induced the increase of cooking loss and optimum cooking time, led to an increase in the hardness and chewiness, and a significant decrease in the adhesiveness. No significant change was observed in the springiness of noodles (p > 0.05). The addition of alkaline salts significantly increased the content of albumin and salt-soluble protein (p < 0.05), while decreased the content of globulin (p < 0.05). Gliadin and glutenin in alkaline noodles decreased to some extent. The band density of the low and medium molecular regions of the protein in noodles was increased, whether or not they were reduced and no obvious band shifts were observed. Alkaline salts had effects on the peak viscosity, minimum viscosity, breakdown, final viscosity, peak time, setback and pasting temperature of alkaline noodles, while the pasting temperature was relatively stable under alkaline conditions. Alkaline salts decreased the content of free SH and led to a membrane-like, more closed structure with fewer ditches. Highlights: Alkaline salts induced increase of cooking loss, optimum cooking time, hardness and chewiness. Alkaline salts increased the content of albumin and salt-soluble protein significantly. Alkaline salts decreased the content of free SH.